THE EFFECT OF SOCIAL MEDIA AND TRUST ON PURCHASE DECISION FOR HANDBODY SCARLETT IN KAMPAR REGENCY - Dini Nursyada; Zamhir Basem; Litra Diantara (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of social media and trust on the decision to buy a scarlet handbody in Kampar Regency, namely the cheerful cosmetics shop, the cosmetic blessings and the cosmetic fatma. The sample in this study were all customers who bought Scarlett handbody products at the cosmetic shop, amounting to 100 customers. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. Simultaneously, social media and truts have an effect on purchasing decisions, based on the partial test results, social media have an effect on purchasing decisions, while trust has no effect on customer purchasing decisions. The closeness of the relationship of the independent variable to the dependent variable is very strong with the contribution of the independent variable to the fixed variable which is 73.0%.